Re-evaluating the Quality of Public Services in Malang City: A Comparative Analysis of Taxpayer Satisfaction - Lestari, Vita Dwi; Kinanti, Kartika Ayu; Afrilia, Nur Khusmiyah (PANGRIPTA, 2024)
This study aims to re-evaluate the quality of public services provided to hotel and restaurant taxpayers in Malang City. Using comparative analysis, this study examines the differences between perceived and expected service quality by taxpayers. Data were collected through a questionnaire survey involving 100 hotel taxpayers and 95 restaurant taxpayers. The survey measured five dimensions of service quality, namely reliability, responsiveness, certainty, empathy, and physical evidence. The results showed that although the majority of service users were satisfied with the quality of service received, there was a significant gap between taxpayers' expectations and perceptions, especially in terms of speed of service and transparency of information. These findings highlight the importance of innovation and the application of digital technology to improve the efficiency and effectiveness of public services, as well as the need to simplify administrative procedures. This study provides strategic recommendations for local governments, especially the Malang City Regional Tax Service Agency (BPPD), to improve service quality through digitalization, improving information systems, and increasing staff capacity. This study also underlines the importance of better communication with the public and developing policies that support transparency and accountability in the delivery of public services.